Dynamics of rotating machines - Friswell, M. I. (Cambridge : Cambridge University Press, 2010)
'This book enables engineers to understand the dynamics of rotating machines, starting from the most basic explanations and then proceeding to detailed numerical models and analysis'--Provided by publisher.
'This book equips the reader to understand every important aspect of the dynamics of rotating machines. Will the vibration be large? What influences machine stability? How can the vibration be reduced? Which sorts of rotor vibration are the worst? The book develops this understanding initially using extremely simple models for each phenomenon, in which (at most) four equations capture the behavior. More detailed models are then developed based on finite element analysis, to enable the accurate simulation of the relevant phenomena for real machines. Analysis software (in MATLAB) is associated with this book, and novices to rotordynamics can expect to make good predictions of critical speeds and rotating mode shapes within days. The book is structured more as a learning guide than as a reference tome and provides readers with more than 100 worked examples and more than 100 problems and solutions'--Provided by publisher.
Introduction -- Introduction to vibration analysis -- Free lateral response of simple rotor models -- Finite element modeling -- Free lateral response of complex systems -- Forced lateral response and critical speeds -- Asymmetric rotors and other sources of instability -- Balancing -- Axial and torsional vibration -- More complex rotordynamic models.
Includes bibliographical references and index.
Keywords: Rotors -- Dynamics; Rotors -- Vibration